Slow magnetic relaxation in a EuCu5 metallacrown. Issue 5 (8th January 2019) - Wang, Jin; Ruan, Ze-Yu; Li, Quan-Wen; Chen, Yan-Cong; Huang, Guo-Zhang; Liu, Jun-Liang; Reta, Daniel; Chilton, Nicholas F.; Wang, Zhen-Xing; Tong, Ming-Liang
Abstract : A Eu III Cu5 metallacrown displays field-induced slow magnetic relaxation, in which the Eu III with diamagnetic ground state enhances the relaxation rates. Abstract : A 3d–4f heterometallic metallacrown with formula of [EuCu5 (quinha)5 (sal)2 (py)5 ]CF3 SO3 ·py·3H2 O (1 ) (H2 quinha = quinaldichydroxamic acid; Hsal = salicylaldehyde) has been synthesized. This complex shows field-induced slow magnetic relaxation via a Raman-like process, where studies of the isostructural LuCu5 (2 ) and YCu5 (3 ) complexes show that the slow dynamics mainly arise from the Cu5 S = 1/2 ground state rather than the Eu III ion. However, the Eu III ion enhances the relaxation rates of the Cu5 unit which likely arises from second-order effects in the formally diamagnetic 7 F0 ground state of Eu III .